Pencatatan dan Penyusunan Laporan Keuangan Berdasarkan SAK EMKM Tahun 2018 Pada UKM Sektor Perdagangan di Kabupaten Bandung - Irene Sukma Lestari Barus; Harry Suharman (FEB Universitas Sultan Ageng Tirtayasa, 2020)
ABSTRACTThis research contributes to the Small and Medium Enterprises in recording business transactions using the Small and Medium Entity Financial Accounting Standards (SAK EMKM) in 2018. Financial statements are made in the form of a Balance Sheet, Income Statement and Notes to Financial Statements . This is a qualitative study conducted to MSEs in Bandung Regency. Sources data from Interview Unstructure and Focus Gorup Discussion. The recording system that has been conducted generally uses a cash basis rather than an accrual basis. The results of this study propose that the recording system carried out consists of a periodic system and an accrual-based pepertual system.